The effect of the north-east ice stream on the Greenland ice sheet in changing climates - Greve, Ralf; Otsu, Shoko
The north-east Greenland ice stream (NEGIS) was discovered as a large fast-flow feature of the Greenland ice sheet by synthetic aperture radar (SAR) imaginary of the ERS-1 satellite. In this study, the NEGIS is implemented in the dynamic/thermodynamic, large-scale ice-sheet model SICOPOLIS (Simulation Code for POLythermal Ice Sheets). In the first step, we simulate the evolution of the ice sheet on a 10-km grid for the period from 250 ka ago until today, driven by a climatology reconstructed from a combination of present-day observations and GCM results for the past. We assume that the NEGIS area is characterized by enhanced basal sliding compared to the "normal", slowly-flowing areas of the ice sheet, and find that the misfit between simulated and observed ice thicknesses and surface velocities is minimized for a sliding enhancement by the factor three. In the second step, the consequences of the NEGIS, and also of surface-meltwater-induced acceleration of basal sliding, for the possible decay of the Greenland ice sheet in future warming climates are investigated. It is demonstrated that the ice sheet is generally very susceptible to global warming on time-scales of centuries and that surface-meltwater-induced acceleration of basal sliding can speed up the decay significantly, whereas the NEGIS is not likely to dynamically destabilize the ice sheet as a whole.